Development and evaluation of pluronic- and methylcellulose-based thermoreversible drug delivery system for insulin. (November 2014) - Nasir, Fazli; Iqbal, Zafar; Khan, Amirzada; Khan, Jamshaid A.; Khan, Abad; Khuda, Fazli; Zakir, Shahida; Yousaf, Nageen; Khan, Ismail; Shah, Yasar; Khan, Muhammad Imran; Shahbaz, Naila
Abstract The objective of the current work was to develop and evaluate thermoreversible subcutaneous drug delivery system for Insulin. Thermoreversible in-situ gel system was developed and evaluated both in-vitro and in-vivo comprising of pluronic F-127 alone or in combination with methylcellulose in different ratios. The drug release kinetics and mechanism was predicted by applying various mathematical models to the in-vitro dissolution data. Rabbits were used as animal model following subcutaneous injection to predict various pharmacokinetic parameters by applying Pk-Summit® software. The in-vitro and in-vivo data revealed that the formulation IPM 15/3 consisting of the pluronic F-127 (15% w/v) and methylcellulose (3% w/v) was the most robust and capable formulation for extending the drug release and maintaining basal plasma insulin level between 10 and 40 µU/ml for 240 h (10 d).